O ateliê do sensível: a fronteira mole entre arte e moda - Mina, Simone da Silva (2017)
The present work discusses the presence of a silence language in fashion elaboration processes, prior to its enrolling in the industrial reproducibility scale, through the work of some creators and the author’s experience with performative installations. The study includes an observation of the studio, as locus of creation, and contributes with points of contact between art and fashion. The art studio goes from the dimension of a space of creation only, to a space of production of presence, revealing that these two areas of the sensible, art and fashion, favor a reflection on the moving of their “frontiers”. The investigation is on the scope of experimentalism, as a site of a reflexive act that unites, in its gesture, aesthetics and poetics, and so to speak, an experiment of micropolitics.